2013
DOI: 10.1080/10916466.2011.576370
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Multi-walled Carbon Nanotubes on Solubility of Methane in Water

Abstract: In this research, the effects of multi-walled carbon nanotubes (NTs) on dissolution of methane in water have been investigated. The tests were performed in a 370 CC vessel at pressures 3 and 5 bar and temperatures of 1-5 ı C. The solution volume was 300 CC. For any solution data of vessel pressure versus time and the total absorption capacity were collected. NTs were dispersed in water by using the sodium dodecyl sulfate (SDS) solution with a concentration of 1 wt% and applying ultrasonic agitation for 25 min.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Results have shown that sodium dodecyl sulfate (SDS) acts reasonably well in this respect (Zhang et al, 2000;Ganji et al, 2007a;Ganji et al, 2007b;Zhang et al, 2007;Zhang and Lee, 2009;Mohammadi et al, 2011;Mohammadi et al, 2013a;Mohammadi et al, 2013b). In this work, pressure-time and temperature-time figures were plotted using kinetic results.…”
Section: Introductionmentioning
confidence: 92%
“…Results have shown that sodium dodecyl sulfate (SDS) acts reasonably well in this respect (Zhang et al, 2000;Ganji et al, 2007a;Ganji et al, 2007b;Zhang et al, 2007;Zhang and Lee, 2009;Mohammadi et al, 2011;Mohammadi et al, 2013a;Mohammadi et al, 2013b). In this work, pressure-time and temperature-time figures were plotted using kinetic results.…”
Section: Introductionmentioning
confidence: 92%
“…Furthermore, the dye diffusion rate in the Al 2 O 3 nanofluid was much faster than in pure water, with the best results obtained at a volume fraction of Al 2 O 3 of 0.5% . Additionally, it has been reported that nanoparticles can increase the solubility of gases. , Given these advantages, it is not surprising that nanofluids are getting attention. Metal nanoparticles, carbon-based nanoparticles, and metal and nonmetal oxide nanoparticles are the three main types of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%